Gambaran Feminisme dalam film Moxie disutradarai oleh Amy Poehler - Tasya Gisele; Irpan Ali Rahman (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2024)
This research purpose is to potray feminism issue that happen in education aspects and handling about gender issues in their environment and experience women’s with feminism values useful in the future. In this research, writer analysis Moxie movie with main problem every character in their school and any problem their happens of that with any people in their school against their feminism community. This Movie tells a story women’s struggle for their rights in their school in context fashion, scholarship, and their right for choose something. Through of every women’s with different background they all cooperate for their position in their school and want feel comfort and don’t want get racism between gender. The writer does analysis this research used Liberal feminism by Betty Friedan methods. Every dialogue in this movie could be useful for this research as a proof relate with the theory and women’s life in the future. Through eight points writer find matches in every dialogue in scene of Moxie movie. After that the writer try to research that be stronger proof for this thesis analyze and useful for understands. The results of this research will explain about gender issue in our environment and women’s can break that without rebel with Liberal feminism method. The writer hopes result of this research can inspire and help any women’s in round of the world. Keywords : Feminism, liberal feminism, movie.